2021
DOI: 10.3390/v13112127
|View full text |Cite
|
Sign up to set email alerts
|

Clusters of SARS-CoV-2 Lineage B.1.1.7 Infection after Vaccination with Adenovirus-Vectored and Inactivated Vaccines

Abstract: A SARS-CoV-2 B.1.1.7 variant of concern (VOC) has been associated with increased transmissibility, hospitalization, and mortality. This study aimed to explore the factors associated with B.1.1.7 VOC infection in the context of vaccination. On March 2021, we detected SARS-CoV-2 RNA in nasopharyngeal samples from 14 of 22 individuals vaccinated with a single-dose of ChAdOx1 (outbreak A, n = 26), and 22 of 42 of individuals with two doses of the CoronaVac vaccine (outbreak B, n = 52) for breakthrough infection ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 53 publications
0
6
0
1
Order By: Relevance
“…These observations persisted after adjustment for country-specific population size, age structure, and GDP distributions, as well as time-varying nonpharmaceutical interventions measured with the Stringency Index, and the dominant circulating SARS-CoV-2 variants. These large-scale epidemiological observations from geographically diverse countries place into a real-world context the existing data from clinical trials and ex vivo functional assays, which suggest that IVV does not confer as robust and durable clinical protection against SARS-CoV-2 as do genetic vaccines, particularly mRNAbased COVID-19 vaccines (Chen et al, 2021, Cheng et al, 2021, de Souza et al, 2021, Earle et al, 2021, Fernandez et al, 2022, Rotshild et al, 2021.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…These observations persisted after adjustment for country-specific population size, age structure, and GDP distributions, as well as time-varying nonpharmaceutical interventions measured with the Stringency Index, and the dominant circulating SARS-CoV-2 variants. These large-scale epidemiological observations from geographically diverse countries place into a real-world context the existing data from clinical trials and ex vivo functional assays, which suggest that IVV does not confer as robust and durable clinical protection against SARS-CoV-2 as do genetic vaccines, particularly mRNAbased COVID-19 vaccines (Chen et al, 2021, Cheng et al, 2021, de Souza et al, 2021, Earle et al, 2021, Fernandez et al, 2022, Rotshild et al, 2021.…”
Section: Discussionmentioning
confidence: 95%
“…On the other hand, IVV are protein-based vaccines purified from chemically inactivated whole viruses that contain spike proteins in both pre-and post-fusion conformations that may impact effectiveness (Heinz and Stiasny, 2021). Antibodies against IVV may wane rapidly (Azak et al, 2021, Saure et al, 2022, especially in the elderly with immune senescence (Karamese and Tutuncu, 2022), and may have significantly reduced neutralization potency against specific SARS-CoV-2 variants of concern (Chen et al, 2021, de Souza et al, 2021, Fernandez et al, 2022.…”
Section: Introductionmentioning
confidence: 99%
“…The N501Y mutation predominantly seen in the studies yielded by our review also lowers the neutralization capacity of the vaccines [ 25 , 69 ]. Infections with the N501Y mutation in the Alpha variant led to low neutralizing antibodies against the AZD1222 vaccine compared to non-Alpha variants [ 14 ].…”
Section: Discussionmentioning
confidence: 97%
“…In Brazil, the effectiveness of ChAdOx1 and CoronaVac/Sinovac was evaluated in two outbreaks of the alpha variant, in a convent and a Long Term Care Facility for the elderly. They observed that vaccination did not prevent people from becoming infected, but there was a reduction in the number of deaths, symptoms and severe cases of the disease, even in this population whose average age was around 77 years, with 1 dose of ChAdOx1 or two from CoronaVac/Sinovac ( 29 ).…”
Section: Alpha Variantmentioning
confidence: 99%